Three new and a known species of the genus Proleptonchus Lordello, 1955 (Nematoda: Leptonchidae) with a diagnostic compendium of the genus - Ahad, Sumaya; Ahmad, Wasim (Zootaxa, 2016)
This paper deals with the description of three new and one known species of the genus Proleptonchus Lordello, 1955. Proleptonchus kazirangus n. sp. from Kaziranga National Park, India is characterized by having 1.08–1.45 mm long body; cap-like, offset, lip region; 7–8 µm long odontostyle and 10–12 µm long odontophore; short, pear-shaped pharyngeal bulb offset by a constriction, occupying about 18–21% of total neck length; female genital system mono-prodelphic; pars dilatata uteri with distinctly sclerotized central lumen containing refringent apophyses; posterior uterine sac 78–112 µm long, with sac-like structure representing a rudimentary oviduct; transverse vulva, short, rounded-conoid tail and males with 31–33 µm long spicules, lateral guiding pieces and seven, regularly spaced ventromedian supplements. P. prerectus n. sp. from Japan is characterized by having 1.18–1.43 mm long body; lip region cap-like, offset by a slight constriction; odontostyle 8 µm, odontophore 9–10 µm; short cylindroid basal bulb offset by a constriction, occupying about 16–20% of total neck length; female genital system mono-prodelphic; pars dilatata uteri with sclerotized refringent apophyses; posterior uterine sac small, 27–36 µm; transverse vulva; a prerectal chamber and short, rounded-hemispheroid tail. P. japonicus n. sp. also from Japan is characterized by having 0.91–1.04 mm long body; lip region cap-like, set off by a slight constriction; odontostyle 5 µm and odontophore 10–11 µm long; pharynx consists of a very slender, non-muscular anterior part, separated from pyriform basal bulb by a constriction, with thickened lumen in posterior region, occupying about 18–20% of total neck length; female genital system mono-prodelphic; posterior uterine sac small, 20–24 µm long; transverse vulva and short, rounded-conoid tail. P. shamimi Bajaj & Bhatti, 1980 is redescribed and its relationship with closely related species is discussed. A diagnostic compendium of all the valid species of Proleptonchus is also provided.